Interactive Data Framework and User Interface for Wisconsin’s Oversize-Overweight Vehicle Permits - Ahmed S. Shatnawi; Nicholas Coley; Hani H. Titi (Data, 2018)
With continuing increases in the number of Oversize-Overweight (OSOW) vehicle permits issued in recent years, the management and analysis of OSOW permit data is becoming more inefficient and time-consuming. Large quantities of archived OSOW permit data are held by Departments of Transportation (DOTs) across the United States, and manual extraction and analysis of this data requires significant effort. In this paper, the authors present a new framework for analyzing Wisconsin’s historic OSOW permit program data. This framework provides an interactive, web-based interface to query the OSOW permit data, link OSOW records to geospatial data features, and dynamically visualize query results. The web-based interface offers scalability and broad accessibility to the data across different DOT divisions, and use cases. Furthermore, a user survey and heuristic evaluation of the interface demonstrate the project’s utility, and identify goals for future system development.